2003
DOI: 10.1002/jsfa.1442
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of falcarinol and the influenceof processing and storage on its content in carrots (Daucus carota L)

Abstract: The concentration-dependent activity of the polyacetylene falcarinol ((9Z)-heptadeca-1,9-dien-4,6-diyn-3-ol), isolated from carrots, was investigated in a bioassay with primary mammary epithelial cells in collagen gels and compared with that of β-carotene, the orange pigment in carrots. Falcarinol showed biphasic activity, having stimulatory effects between 0.01 and 0.05 µg ml −1 and inhibitory effects between 1 and 10 µg ml −1 , whereas β-carotene showed no effect in the concentration range 0.001-100 µg ml −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
147
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(161 citation statements)
references
References 41 publications
11
147
0
3
Order By: Relevance
“…and other Araliaceae. It is considered a natural pesticide protecting roots from fungal diseases, and displayed some extent of activity against certain types of cancer [369]. Production of this compound has been reported by a strain of Paecilomyces sp.…”
Section: Miscellaneous Compoundsmentioning
confidence: 99%
“…and other Araliaceae. It is considered a natural pesticide protecting roots from fungal diseases, and displayed some extent of activity against certain types of cancer [369]. Production of this compound has been reported by a strain of Paecilomyces sp.…”
Section: Miscellaneous Compoundsmentioning
confidence: 99%
“…Bolero, Rodelika and Fancy) were stored at 1 o C and 98% RH falcarinol content was initially in the range 22.3 -24.8 mg/kg. Levels were largely unchanged during the first month but subsequently declined by nearly 35% after 120 days storage, which the authors attribute to a change in the balance between biosynthesis and degradation [62]. However in a study in which polyacetylene content in carrot roots of six Nantes cultivars (cvs.…”
Section: Harvest and Post-harvest Management Of Carrotmentioning
confidence: 96%
“…Variation in carotenoid profile has been reported with some carrot cultivars primarily accumulating lutein whilst others primarily accumulated a and 1 carotene [157]. Levels of individual polyacetylenes differ between different carrot varieties [4,30,34,62,79,105,106], and between different members of the Apiaceae family [38,192]. In an analysis of 5 members of the Apiaceae, falcarinol was found in all investigated taxa except parsley.…”
Section: Crop and Cultivarmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that this this model is a very sensitive screening model for milk-derived bioactives (Norup et al, 1997;Weber et al, 1997 and2000;Purup et al, 1999Purup et al, , 2000Purup et al, and 2002Ellis et al, 2000;Lametsch et al, 2000;Sejrsen et al, 2000;Hansen et al, 2003;Thorn et al, 2006;Fusi et al, 2008). Groups of mammary epithelial cells are isolated from parenchymal tissue by enzymatic treatment and precipitation and these isolated organoids are then cultured in collagen gels, allowing the cells to proliferate in three dimensions.…”
Section: Cell-based Models Of the Mammary Glandmentioning
confidence: 99%